1999
DOI: 10.1038/sj.leu.2401257
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency of TEL-AML1 in relapsed acute lymphoblastic leukemia supports a favorable prognosis for this genetic subgroup

Abstract: The long-term outcome of children with TEL-AML1-positive acute lymphoblastic leukemia (ALL) is uncertain. Although studies of newly diagnosed cases have indicated that the TEL-AML1 fusion confers a favorable prognosis, analyses of relapsed cases have suggested that this may not be true. Because of treatment implications for this subgroup of patients, we have now analyzed 49 cases of relapsed ALL for the presence of TEL-AML1. Only 10% of these cases expressed the fusion, compared to 20-25% of newly diagnosed AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 13 publications
5
48
1
Order By: Relevance
“…However, none of the major studies disputed better outcome of TEL/AML1-positive patients. [2][3][4] In this respect, disturbing phenomenon emerged in retrospective studies on relapsed ALL. Not only do the TEL/AML1-positive leukaemias relapse but in some studies their relapse rate appears to be unexpectedly high.…”
Section: To the Editormentioning
confidence: 99%
“…However, none of the major studies disputed better outcome of TEL/AML1-positive patients. [2][3][4] In this respect, disturbing phenomenon emerged in retrospective studies on relapsed ALL. Not only do the TEL/AML1-positive leukaemias relapse but in some studies their relapse rate appears to be unexpectedly high.…”
Section: To the Editormentioning
confidence: 99%
“…6 Investigators from St. Jude and from the DFCI also demonstrated a very low frequency of TEL-AML1 in patients with relapsed ALL, consistent with the excellent outcome of patients with this translocation. 7,8 Despite the plethora of studies that suggest that TEL-AML1 is an independent favorable predictor of outcome and should be used in risk classification, questions remain regarding its true impact. 9 For example, some reports demonstrated a high incidence (20% to 24%) of the TEL-AML1 fusion in relapsed cases of ALL, thereby casting doubt as to the prognostic significance of this genetic alteration.…”
Section: Introductionmentioning
confidence: 99%
“…high initial WBC, early relapse and death) are general features of this subgroup. In fact they seem to differ from the characteristics of TEL/AML1-positive patients generally described in the literature (Nakao et al, 1996;Borkhardt et al, 1997;Loh et al, 1998;Seeger et al, 1998;Rubnitz et al, 1999;Zuna et al, 1999). However, studies describing the incidence of the TEL/AML1 fusion transcript in relapsed ALL patients did not analyse these characteristics.…”
Section: Discussionmentioning
confidence: 77%
“…Selection bias in our study may be a cause of this discrepancy. But other studies also reported a normal incidence of about 20± 24% Seeger et al, 1998) or a slightly lower incidence of 19% (Nakao et al, 1996;Rubnitz et al, 1999;Zuna et al, 1999) of TEL/AML1 fusion in relapsed patients. In these studies, the analyses were mainly carried out on leukaemic cells collected at relapse and the translocation may have occurred during therapy; at initial diagnosis, the leukaemic cells might have been negative for a TEL/AML1 fusion transcript.…”
Section: Discussionmentioning
confidence: 92%